Optimalisasi akses pelayanan kesehatan oleh kaum dhuafa dan manajemen data pada Rumah Relawan Dhuafa berbasis web di Kabupaten Pelalawan Provinsi Riau - Siska Mayang Sari; Herianto Herianto; Raja Fitrina Lestari (Unri Conference Series: Community Engagement, 2022)
Poverty is a social problem in society, especially in developing countries. The poor, also known as the dhu'afa in Indonesia, is a component of society that cannot be isolated and receive guaranteed protection from the state. The government carries out work programs to reduce poverty and provide services that can be reached by all levels of society. Non-Governmental Organizations (NGOs) play a role in assisting the government in carrying out its programs and serving marginal groups (including the poor). The Rumah Relawan Dhuafa Foundation is an NGO in Pelalawan district, Riau with limited facilities and volunteer skills that have carried out activities to facilitate the poor in obtaining health services. This community partnership program activity aims to overcome the problems experienced by the Rumah Relawan Dhuafa. Community service programs carried out during June September 2022 in the form of 1) Designing an administrative information system for the Rumah Relawan Dhuafa, 2) Designing an application for the Rumah Relawan Dhuafa, 3) Providing counseling, training, and guidance on SOPs for service/patient admissions, and 4) Providing counseling, Training and mentoring for volunteers related to first aid handling skills. After a series of service activities were carried out, the results obtained were the formation of a home for poor volunteers, increased knowledge and skills of volunteers regarding the use of application systems, preparation of standard operating procedures for patient acceptance, and first handling of accidents, those will be used by the volunteer in RRD to facilitated the Dhuafa to receive the health care services.